2013
DOI: 10.1186/1471-2474-14-297
|View full text |Cite
|
Sign up to set email alerts
|

Independent associations of socioeconomic factors with disability and pain in adults with knee osteoarthritis

Abstract: BackgroundThe purpose of this study is to explore the relationship between function, pain and stiffness outcomes with individual and community socioeconomic status (SES) measures among individuals with radiographic knee osteoarthritis (rOA).MethodsCross-sectional data from the Johnston County Osteoarthritis Project were analyzed for adults age 45 and older with knee rOA (n = 782) and a subset with both radiographic and symptomatic knee OA (n = 471). Function, pain and stiffness were measured using the Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 49 publications
7
63
0
2
Order By: Relevance
“…For example, the prevalence of symptomatic knee OA was higher among subjects who received less education compared with those who received more education (26,27) and among those who lived in communities with high poverty rates (28). Our study also demonstrated that symptomatic knee OA was more common among persons living in rural areas compared with urban areas in China; this finding was consistent with those of previous studies SYMPTOMATIC KNEE OSTEOARTHRITIS IN CHINA 651 (13,14).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For example, the prevalence of symptomatic knee OA was higher among subjects who received less education compared with those who received more education (26,27) and among those who lived in communities with high poverty rates (28). Our study also demonstrated that symptomatic knee OA was more common among persons living in rural areas compared with urban areas in China; this finding was consistent with those of previous studies SYMPTOMATIC KNEE OSTEOARTHRITIS IN CHINA 651 (13,14).…”
Section: Discussionsupporting
confidence: 82%
“…Our study also demonstrated that symptomatic knee OA was more common among persons living in rural areas compared with urban areas in China; this finding was consistent with those of previous studies SYMPTOMATIC KNEE OSTEOARTHRITIS IN CHINA 651 (13,14). Given that residents living in less-developed or rural areas often have limited resources, including fewer clinics, safe options for public transportation, community centers, and safe places to exercise, as well as poorly kept sidewalks and less access to safe streets (28)(29)(30), studies of the impact of symptomatic knee OA on the residents in these communities are urgently needed. We demonstrated an apparent geographic variation in the prevalence of symptomatic knee OA in China.…”
Section: Discussionsupporting
confidence: 81%
“…The key demographic factors considered important to include in the Standard Set were patient age, sex, and socioeconomic status 35, 36, 37. Although many different indicators of socioeconomic status have been published in the literature, only education level as defined by the International Standard Classification of Education can be considered consistent across countries and cultures for international use 36, 38.…”
Section: Resultsmentioning
confidence: 99%
“…The Johnston County Project is an ongoing, longitudinal, population-based study of knee and hip osteoarthritis that includes both rural and urban communities in North Carolina. [5] Callahan et al [6] have shown that both low levels of education and living in a community with a household poverty rate greater than 25% are independently associated with the risk for radiographic and symptomatic knee osteoarthritis. Cleveland et al [5] found that individuals with knee osteoarthritis who are at the highest risk of developing disability and pain have lower SES.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Callahan et al [6] have shown that both low levels of education and living in a community with a household poverty rate greater than 25% are independently associated with the risk for radiographic and symptomatic knee osteoarthritis. Cleveland et al [5] found that individuals with knee osteoarthritis who are at the highest risk of developing disability and pain have lower SES. Persons working in non-managerial occupations are more likely to have worse pain scores on the Western Ontario and McMaster Universities Index of Osteoarthritis compared to individuals in managerial positions.…”
Section: Discussionmentioning
confidence: 99%